2004
DOI: 10.1128/aac.48.8.3196-3199.2004
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antimalarial Compounds Isolated in a Survey of Self-Medicative Behavior of Wild Chimpanzees in Uganda

Abstract: Following a veterinary and behavioral survey of chimpanzees from a natural population in Uganda, leaf samples of Trichilia rubescens were collected because of the unusual method of ingestion observed. The methanolic crude extract of T. rubescens leaves exhibited significant antimalarial activity in vitro. Bioassaydirected fractionation provided two new limonoids, trichirubines A and B. A greater understanding of the role of secondary compounds in the primate diet may be helpful in recovering naturally occurrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 21 publications
3
54
0
5
Order By: Relevance
“…PSMs in V. amygdalina also have been effective at controlling nematodes that cause significant losses of livestock in the tropics (Plotkin, 2000). Other plants selected by chimpanzees have medicinal effects in the amounts (doses) consumed: limonoids in Trichilia rubescens have antimalarial activity (Krief et al, 2004), and methoxypsoralen in Ficus exasperata is a strong antibiotic (Rodriguez and Wrangham, 1993).…”
Section: Self-medicationmentioning
confidence: 99%
“…PSMs in V. amygdalina also have been effective at controlling nematodes that cause significant losses of livestock in the tropics (Plotkin, 2000). Other plants selected by chimpanzees have medicinal effects in the amounts (doses) consumed: limonoids in Trichilia rubescens have antimalarial activity (Krief et al, 2004), and methoxypsoralen in Ficus exasperata is a strong antibiotic (Rodriguez and Wrangham, 1993).…”
Section: Self-medicationmentioning
confidence: 99%
“…According to Albuquerque and Hanazaki (2008) this approach intends to evaluate the use of secondary metabolites by animals or other non-nutritional substances from plants, aiming to combat diseases or controlling them, as it can be seen in the works developed by Carrai (2003) and Krief (2004). In the latter, it was observed that leaves of Trichilia rubescens Oliv.…”
Section: The Ecological Approachmentioning
confidence: 99%
“…Um caminho recentemente apontado para a descoberta de novos fármacos é baseado nos estudos de comportamento animal com primatas (Krief et al, 2004), ou abordagem etológica. Esta abordagem tem como orientação avaliar a utilização de metabólitos secundários por animais, ou outras substâncias não nutricionais dos vegetais, com a fi nalidade de combater doenças ou controlá-las (Huffman, 2003;Carrai et al, 2003).…”
Section: Introductionunclassified
“…Folhas de Trichilia rubescens Oliv., consumidas por chimpanzés de Uganda, revelaram atividade antimalárica in vitro suportando a hipótese de que a dieta de chimpanzés contém metabólitos secundários de interesse médico (Krief et al, 2004). Entretanto, uma das defi ciências na interpretação da automedicação por animais reside em saber se a ingestão é intencional ou secundariamente como resultado do simples ato de se alimentar (Huffman, 2001(Huffman, , 2003.…”
Section: Introductionunclassified